Feeding the Russian fur trade provisionment of the Okhotsk seaboard and the Kamchatka Peninsula, 1639-1856 - Gibson, James R. (University of Wisconsin Press, 1969)
Gives full account of the changing geography of the Okhotsk seaboard and Kamchatka peninsula as well as difficulties of supplying food to these far distant areas.